MeCP2_E1 N-terminal modifications affect its degradation rate and are disrupted by the Ala2Val Rett mutation. (27th July 2017) - Sheikh, Taimoor I; de Paz, Alexia Martínez; Akhtar, Shamim; Ausió, Juan; Vincent, John B
Abstract: Methyl CpG-binding protein 2 (MeCP2), the mutated protein in Rett syndrome (RTT), is a crucial chromatin-modifying and gene-regulatory protein that has two main isoforms (MeCP2_E1 and MeCP2_ E2) due to the alternative splicing and switching between translation start codons in exons one and two. Functionally, these two isoforms appear to be virtually identical; however, evidence suggests that only MeCP2_E1 is relevant to RTT, including a single RTT missense mutation in exon 1, Ala2Val. Here, we show that N-terminal co- and post-translational modifications differ for MeCP2_E1 and MeCP2_E1-Ala2Val, which result in different protein degradation rates in vitro . We report complete N-methionine excision (NME) for MeCP2_E1 and evidence of excision of multiple alanine residues from the N-terminal polyalanine stretch. For MeCP2_E1-Ala2Val, we observed only partial NME and N-acetylation (NA) of either methionine or valine. The localization of MeCP2_E1 and co-localization with chromatin appear to be unaffected by the Ala2Val mutation. However, a higher proteasomal degradation rate was observed for MeCP2_E1-Ala2Val compared with that for wild type MeCP2_E1. Thus, the etiopathology of Ala2Val is likely due to a reduced bio-availability of MeCP2 because of the faster degradation rate of the unmodified defective protein. Our data on the effects of the Ala2Val mutation on N-terminal modifications of MeCP2 may be applicable to Ala2Val mutations in other disease genes for which no etiopathological mechanism has been established.